TRIAD CONFERENCE: IS IT A MORE EFFECTIVE WAY OF INVOLVING PARENTS AND STUDENTS? - Lam, Y.L. Jack; Peake, Dale (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1997)
ABSTRACT. The present paper documents a relatively new approach adopted by a school to involve parents and students in the formulation of individualized educational goals and plans, in the collection of data to generate comprehensive profiles about the students, and, in the final assessment of students’ performance. This paper assesses the effectiveness of the whole operation after one year. Feedback from teachers, parents, and students suggested that the three stages of the triad conference model were intimately related. All parties seemed to be satisfied with the outcome, but parents felt that the classroom teachers still dominated the conferences when the three parties were supposedly equal partners in the children’s education. This could register initial adjustment difficulties teachers experienced in the transition from the traditional parentteacher interviews to the more innovative format of engaging parents and students in all critical stages of the educational process. RÉSUMÉ. Cet article illustre une démarche relativement nouvelle adoptée par une école afin de faire participer les parents et les élèves à la formulation de buts et de plans scolaires personnalisés, à la collecte de données pour brosser un portrait assez complet des élèves et enfin à l’évaluation du rendement des élèves. L’auteur évalue l’efficacité du processus au bout d’un an. La rétroaction des enseignants, des parents et des élèves incite à croire que les trois étapes du modèle de conférence à trois sont intimement liés. Toutes les parties semblent satisfaites du résultat, mais les parents estiment que les professeurs dominent toujours les conférences alors que les trois parties sont censées être des partenaires égaux dans l’éducation des enfants. Cela pourtait expliquer les difficultés préliminaires que les enseignants ont éprouvées à s’ajuster à la formule plus novatrice qui consiste à faire participer les parents et les élèves à toutes les étapes critiques du processus pédagogique.